Organisation informelle et identité : de la théorie des organisations à l'économie politique de l'entreprise. (June 2016) - Chassagnon, Virgile; Baudry, Bernard
In this paper the authors defend the idea according to which the economic theories of the firm could be astutely enriched by specific theoretical developments of organization theories. In this view, they focus on two crucial research questions for the political economics of the firm: (1) the informal organization of the firm; and (2) social identity in the firm. This analysis allows to show the strong limitations of classical economic theory of the firm and to contribute to the reworking of a political economy of the firm.